Burden of cataracts in developing countries: a trend analysis based on data from China, 1990 to 2021 - Cancan Zhang; Pingping Li; Lurun Yu; Lu Li (Frontiers in Medicine)
ObjectiveTo investigate the trends in cataract-related blindness and vision impairment burden among cataract patients in China, the largest developing country, from 1990 to 2021, providing evidence to inform future cataract prevention and control strategies in developing countries.Patients and methodsThis study utilized data from the Global Burden of Disease (GBD) 2021 database to assess the prevalence, age-standardized prevalence rates (ASPR), and years lived with disability (YLDs) associated with cataract-related blindness and visual impairment in China and other regions from 1990 to 2021. Joinpoint regression, decomposition analysis, and ARIMA modeling were employed to analyze trends and predict future disease burden.ResultsFrom 1990 to 2021, the number and crude rate for cataract related blindness and visual impairment increasing significantly in China. The age-standardizes rate increased from 878.30 to 989.58 per 100,000 population for cataract prevalence, and from 73.40 to 61.39 per 100,000 population for cataract YLDs. The majority of number of prevalence and YLDs are concentrated in the 65–89 age range. Women had higher cataract prevalence and YLDs than men. Population aging is the primary driver of the growing burden of cataract, contributing 73.12% and 98.3% to the increases in prevalence and YLDs, respectively. By 2035, the crude prevalence rate and crude YLDs rate of cataracts are projected to increase by 26.06% and 23.03%, respectively, compared to 2021. The age-standardized prevalence and YLDs rate attribute to cataract in China were lower than global averages and ranked third among neighboring countries.ConclusionDespite advancements in cataract treatment that have alleviated some of the disease burden, population growth and aging continue to drive the increasing prevalence of cataract-related vision impairment in China. Addressing gender disparities and improving access to cataract surgery and preventive care are crucial for reducing this growing burden.